2020
DOI: 10.1016/j.isci.2020.101095
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Enhanced Piezo-Catalysis for Hydrogen Generation and Water Treatment at the Ferroelectric Curie Temperature

Abstract: Hydrogen can contribute significantly to the energy mix of the near future, as it is an attractive replacement for fossil fuels due to its high energy density and low greenhouse gas emission. A fascinating approach is to use the polarization change of a ferroelectric due to an applied stress or temperature change to achieve piezo-or pyro-catalysis for both H 2 generation and wastewater treatment. We exploit low Curie temperature (T c ) ferroelectrics for polarization-driven electrochemical reactions, where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 83 publications
1
50
0
Order By: Relevance
“…In addition, the highest and most distinct sono-piezo-catalytic hydrogen and CO production were observed at a working temperature of 38 o C, which correlates with the T c of PZTN, as shown in Figure 3B. It has previously been discussed that pyro-catalytic H 2 generation activity is greatest near the T c [22], and this work demonstrates that is also applied to CO production. By optimization of the piezo-catalytic effect of PZTN in relation to its T C and in the presence of ultrasound, a promising piezo-catalytic CO 2 reduction rate of 789 µmol/g/h is achieved, which is much larger than the those obtained from the pyro-catalytic effect using Bi 2 WO 6 (16.5 µmol/g/h) [35].…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…In addition, the highest and most distinct sono-piezo-catalytic hydrogen and CO production were observed at a working temperature of 38 o C, which correlates with the T c of PZTN, as shown in Figure 3B. It has previously been discussed that pyro-catalytic H 2 generation activity is greatest near the T c [22], and this work demonstrates that is also applied to CO production. By optimization of the piezo-catalytic effect of PZTN in relation to its T C and in the presence of ultrasound, a promising piezo-catalytic CO 2 reduction rate of 789 µmol/g/h is achieved, which is much larger than the those obtained from the pyro-catalytic effect using Bi 2 WO 6 (16.5 µmol/g/h) [35].…”
Section: Resultssupporting
confidence: 63%
“…and ~ 1.23 V[78], respectively. While it is difficult to measure the local surface potential of the single piezoelectric particle during the ultrasound, our recent work[22] has demonstrated that the barium strontium titanate (Ba 0.75 Sr 0.25 TiO 3 ) with the comparable ferroelectric polarisation has the ability to split the water for the H 2 generation with the application of ultrasound. The piezoelectric potential can be estimate by…”
mentioning
confidence: 99%
“…c Working mechanism of BTS-GFF/PVDF sensors. d Effect of T c on polarization [ 39 ] and electric responses of sensors under different working temperature …”
Section: Resultsmentioning
confidence: 99%
“…When the force is released, the internal electric field disappears, resulting in a smaller reverse current [ 34 ]. When the working temperature of the sensor is close to the T c, the internal spontaneous polarization of the films is more likely to rotate under the action of external force [ 39 ], resulting in more induced charges and larger output signal (Fig. 3 d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation